Multi-objective optimization in incremental sheet forming of Ti-6Al-4V alloy using grey relational analysis method. (August 2022) - Ajay, C Veera; Elangovan, S; Pratheesh Kumar, S; Manisekar, K
Incremental sheet forming is a novel approach and advanced manufacturing process in industries, where it is capable of producing complex geometrical components with high accuracy. In this study, Ti-6Al-4V material used in aircraft, naval ships, spacecraft, armour plating and missiles was considered to determine the formability in the incremental sheet forming process. A 20 set of experiments were conducted considering three process variables such as tool rotational speed, step depth and feed rate on the response variables such as formed wall thickness, surface roughness, thrust force and wall angle. The process parameters are optimized using the grey relational analysis method to achieve a better quality of products. By execution multi-objective optimization using grey relational analysis, it is observed that 200 r/min tool rotational speed, 0.1 mm step depth and 2000 mm/min feed rate are optimum parameter settings.